2021
DOI: 10.1111/ecc.13424
|View full text |Cite
|
Sign up to set email alerts
|

'The experience of spirituality in family caregivers of adult and elderly cancer patients receiving palliative care: A meta‐synthesis'

Abstract: Introduction: Spirituality is a multidimensional aspect of human experience. In the context of palliative care, it is an individual resource that can be used to cope with illness and to assign new meanings to suffering. Qualitative studies that aim to investigate the experience of spirituality and the needs of family caregivers in this context are rare.Objective: This meta-synthesis aimed to synthesise qualitative studies on the experience of spirituality in family caregivers of adult and elderly cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
1
19
0
8
Order By: Relevance
“…Another study similarly identified this ambivalence in the anticipatory grieving of caregivers [ 6 ]. Our results are also consistent with other research highlighting that family caregivers may experience significant spiritual, existential, and emotional suffering in their journey toward the end of life [ 7 , 9 , 20 ]. We found that caregivers tried to suppress their feelings to demonstrate strength to the patient, but, as in other studies [ 6 , 28 , 30 , 34 ], feelings of loneliness and helplessness were common.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study similarly identified this ambivalence in the anticipatory grieving of caregivers [ 6 ]. Our results are also consistent with other research highlighting that family caregivers may experience significant spiritual, existential, and emotional suffering in their journey toward the end of life [ 7 , 9 , 20 ]. We found that caregivers tried to suppress their feelings to demonstrate strength to the patient, but, as in other studies [ 6 , 28 , 30 , 34 ], feelings of loneliness and helplessness were common.…”
Section: Discussionsupporting
confidence: 92%
“…Double awareness may also be sustained when family caregivers are dealing with the impending death of a patient with advanced cancer. When there is adequate support, caregiving at the end of life can be a transformative and spiritual experience [ 20 ]. However, few studies have drawn attention to the experience of family caregivers providing care to a family member with advanced cancer at the end of life and its connections to spiritual and existential concerns, and there have been no such studies with Brazilian family caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the findings by Benites et al, (2021) synthetised that caregivers experience spirituality in a way to reach new meaning in life and suffering, constituting simultaneously a transformative experience and an important resource. Spirituality may play this paramount role in life transitions (Martins & Caldeira, 2021).…”
Section: A Commentary On Benites Et Al (2021) "mentioning
confidence: 96%
“…We are writing this commentary on the paper 'The experience of spirituality in family caregivers of adult and elderly cancer patients receiving palliative care: A meta-synthesis' (Benites et al, 2021) recently published in European Journal of Cancer Care. This paper reports a meta-synthesis of the experience of spirituality in family caregivers in cancer patients undergoing palliative care.…”
Section: A Commentary On Benites Et Al (2021) "mentioning
confidence: 99%
“…A literatura mostra que os familiares das pacientes também acreditam que a fé e o senso religioso podem levar à cura do câncer de mama. Eles também apoiam a crença da mulher em uma Força Superior que comanda a harmonia do universo, um Criador misericordioso que personifica a bondade, o que faz com que também acabem se utilizando dessa fonte como recurso para se fortalecerem frente aos seus próprios sentimentos de desamparo (Araújo & Nascimento, 2004;Benites et al, 2021).…”
Section: Fatores Facilitadores Ao Lidar Com a Doença E O Tra-tamento Da Mãeunclassified